2012
DOI: 10.1128/ec.00250-12
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Class I Transcription Factor A (CITFA) Subunit That Is Indispensable for Transcription by the Multifunctional RNA Polymerase I of Trypanosoma brucei

Abstract: cTrypanosoma brucei is the only organism known to have evolved a multifunctional RNA polymerase I (pol I) system that is used to express the parasite's ribosomal RNAs, as well as its major cell surface antigens, namely, the variant surface glycoprotein (VSG) and procyclin, which are vital for establishing successful infections in the mammalian host and the tsetse vector, respectively. Thus far, biochemical analyses of the T. brucei RNA pol I transcription machinery have elucidated the subunit structure of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
68
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(74 citation statements)
references
References 38 publications
(42 reference statements)
5
68
0
Order By: Relevance
“…To analyze specific functions of individual subunits, we attempted to silence the expression of each subunit gene. Our previous results demonstrated that CITFA2 and CITFA7 are essential for RNA pol I transcription and trypanosome viability (13,21). We also found that three of the eight subunits are required to maintain the integrity of the complex (T. N. Nguyen and A. Günzl, unpublished results).…”
mentioning
confidence: 94%
See 3 more Smart Citations
“…To analyze specific functions of individual subunits, we attempted to silence the expression of each subunit gene. Our previous results demonstrated that CITFA2 and CITFA7 are essential for RNA pol I transcription and trypanosome viability (13,21). We also found that three of the eight subunits are required to maintain the integrity of the complex (T. N. Nguyen and A. Günzl, unpublished results).…”
mentioning
confidence: 94%
“…S1 in the supplemental material) has two cassettes, a C-terminal tagging module and a selectable marker cassette. It is a direct derivative of pCITFA7-HA-BLA (21) and was obtained by replacing the T. brucei RPA1 3= gene flank with Tc3 using the vector's XhoI and ClaI restriction sites. Furthermore, our tagging vectors are derived from pBluescript II SK(ϩ), which has a T7 promoter that, after integration into an endogenous allele, could lead to overexpression of downstream genes in T7 RNA polymerase-expressing sm BF and 29-13 PF cells.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…If one imagines VEX1 as a gatekeeper for entry to an ESBassociated VSG transcription "center," then loss of VEX1 would allow a "free-for-all" entry of additional BESs within the ESBassociated center and access to the transcription factors housed within it [Pol I, class I transcription factor A (CITFA), or nucleoplasminlike protein (NLP) (12,20), and possibly others], resulting in increased transcription of VSGs at the newly associated BESs. Conversely, overabundance of VEX1 would establish additional gated centers for VSG expression (which might not necessarily coincide with the ESB).…”
mentioning
confidence: 99%